FACTORS RELATED TO PATERNAL POSTNATAL DEPRESSION (PPND) - Lestari, Puji; Mulansari, Surahmah Asti; Mawarti, Retno (LPPM Universitas Prima Nusantara Bukittinggi, 2020)
Introduction: Previously, perinatal depression was only associated with mothers, so paternal depression was not widely recognized and was not well studied.Purpose: The purpose of this scoping review is to map the available evidence relating to factors related to the postnatal patternal depression (PPND).Methods: The authors identify studies that explain the factors related to the PPND from two databases (PubMed and Science Direct). The search was limited to studies in English, and was published in the period 2010-2019. PRISMA Flowchart is used to identify relevant studies. In this review, the study design of the article is not limited. Provided the article deals with factors related to PPND.Results: In this scoping review eight relevant articles were found for review. Then obtained several factors associated with the incidence of paternal depression in the postnatal period, then from the factors obtained mapping. Three themes were obtained, namely psychosocial factors (parenting distress, infant problems, social support, father's sleep quality, subjective birth experience, depression in partners, and relationships with partners), demographic factors (family income / economy, and experienced father), and the father's physical and mental health history (Previous history of mental illness, history of infertility treatment, and pressure or anxiety in the antenatal period).Conclusion: Among the eight articles, the most frequent factors are family income/economy (4 articles), history of mental health before becoming a father (4 articles), problems in infants (3 articles), social support (3 articles) articles, relationship with partners (3 articles).